Pencak Silat and Traditional Games to Prevent Bullying in Elementary Schools - Tommy Soenyoto; Agus Darmawan; Bhayu Billiandri; Nadiya Arawinda Andar; Adi S; Adiska Rani Ditya Candra; Sri Indah Ihsani; Made Bang Redy Utama (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2025)
Violence and bullying in schools are serious issues that threaten student safety and character development. Physical Education teachers play a strategic role in building student resilience through appropriate approaches. This community service activity aims to equip teachers with physical and mental skills to deal with violence through pencak silat and traditional sports training that instill values of empathy, resilience, and self-control. The activity methods include coordination, socialization, material development, a pretest, two days of theoretical and practical training, three weeks of mentoring, a posttest, and a final evaluation. Data collection was conducted using an online questionnaire to measure participants' understanding. The activity was attended by Physical Education teachers from the Gunungpati sub-district, with results showing an increase in participants' understanding and skills in addressing bullying and violence in the school environment. This program also encourages teachers to become agents of change capable of creating a safe, inclusive, and supportive learning environment for student character development. The conclusion of this activity demonstrates the effectiveness of a culture-based self-defense approach in character education.